2008
DOI: 10.1158/0008-5472.can-08-1861
|View full text |Cite
|
Sign up to set email alerts
|

Cranial Irradiation Alters the Behaviorally Induced Immediate-Early Gene Arc (Activity-Regulated Cytoskeleton-Associated Protein)

Abstract: Therapeutic irradiation of the brain is commonly used to treat brain tumors but can induce cognitive impairments that can severely affect quality of life. The underlying mechanisms responsible for radiation-induced cognitive deficits are unknown but likely involve alterations in neuronal activity. To gain some mechanistic insight into how irradiation may affect hippocampal neurons known to be associated with cognitive function, we quantitatively assessed the molecular distribution of the behaviorally induced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(99 citation statements)
references
References 53 publications
4
95
0
Order By: Relevance
“…Although their morphology varies widely, likely reflecting functional diversity, changes in spine density positively correlate with cognitive performance (31). The capability of dendritic spines to rapidly respond to transmembrane signals, including those associated with behavior, hormonal status, and synaptic activity and various forms of stress, indicate their critical role in learning and memory (32,33). The fact that radiation exposure leads to reduced spine density and, in particular, inhibits the formation of immature filopodia, is consistent with the adverse neurocognitive sequlae documented in brain cancer survivors subjected to cranial radiotherapy (1,34).…”
Section: Discussionmentioning
confidence: 99%
“…Although their morphology varies widely, likely reflecting functional diversity, changes in spine density positively correlate with cognitive performance (31). The capability of dendritic spines to rapidly respond to transmembrane signals, including those associated with behavior, hormonal status, and synaptic activity and various forms of stress, indicate their critical role in learning and memory (32,33). The fact that radiation exposure leads to reduced spine density and, in particular, inhibits the formation of immature filopodia, is consistent with the adverse neurocognitive sequlae documented in brain cancer survivors subjected to cranial radiotherapy (1,34).…”
Section: Discussionmentioning
confidence: 99%
“…Sweet et al (2014) found persistent (1 -12 months) decreases in ICAM-1 after ≄ 10 cGy whole-body irradiation of mice with 1 GeV/n protons with a pronounced sex difference; specifically, females were sensitive while males were not. Rosi et al (2008) and York et al (2012) found significant increases in activated microglia numbers (x-rays and protons) that were correlated with reductions in behaviorally-induced gene expression. Poulose et al (2011) observed astrocyte activation (rat hippocampus) after 16 O exposure accompanied by altered neurotrophic factor signaling, and Sanchez et al (2010) reported reductions in cultured human astrocyte glutamate transport following 1 H, 12 C, and 56 Fe irradiation.…”
Section: Neuroinflammationmentioning
confidence: 94%
“…The behaviorally-induced immediate early gene Arc was investigated by Rosi et al (2008Rosi et al ( , 2010 and Raber et al (2013) for its expression in the dentate gyrus of mice. Both messenger RNA and protein levels in neurons showed behaviorally-induced upregulation which was inhibited by exposure to X-rays and low doses of 56 Fe ions.…”
Section: H Molecular Marker Changesmentioning
confidence: 99%
“…34,46,73,89 Of particular therapeutic relevance are the effects of radiation on the oligodendrocytic lineage.…”
Section: Impact Of Radiation On Neurogenesis and Neuronal Functionmentioning
confidence: 99%